Potensi MOL Dalam Pengelolahan Lingkungan Tercemar Limbah Rumah Tangga - Wan Siti Humaira; Yocelyn Nareswari; Riski Amelia Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Background: The increasing volume of household waste, including solid organic waste and domestic wastewater (greywater), poses a serious threat to environmental sanitation and contributes to the spread of infectious diseases. As an ecological restoration strategy, the use of Local Microorganisms (MOL) derived from food waste offers a sustainable approach to reducing waste at its source. Objective: To critically review the mechanisms of microbial waste decomposition, the diversity of decomposer bacterial colonies, and the direct implications of sanitation practices on family health. Methods: This study employed a systematic literature review by synthesizing primary data from 10 scientific articles focusing on applied microbiology and environmental health. Results: The findings indicate that the efficiency of organic waste biodegradation is strongly influenced by the density of functional microbial populations. Carbohydrate-rich substrates, such as cooked rice, were found to promote decomposer microbial populations of up to 8.36 × 10? CFU/mL, predominantly consisting of phosphate-solubilizing bacteria (Citrobacter freundii) and nitrogen-fixing bacteria (Pseudomonas sp.). In domestic wastewater management, filtration systems generally failed due to insufficient hydraulic retention time and inadequate sanitation infrastructure. Furthermore, dug wells located less than 10 meters from wastewater infiltration areas were associated with biological contamination by Total Coliform, an indicator of fecal pollution.